SINTESIS DAN KARAKTERISASI SILIKA GEL DARI LIMBAH ABU SEKAM PADI(Oryza Sativa) DENGAN VARIASI KONSENTRASI PENGASAMAN - Ismiati Sholikha, Friyatmoko W. K., Erma Dewi Sri Utami, Listiyanti, dan DewiWidyaningsih (Pelita - Jurnal Penelitian Mahasiswa UNY, 2010)
The research about synthesis and characterization of gel silica from ash rice husk(Oryza Sativa) with variation of acid concentration aim to know to earn or doesn't silicaof gel synthesis from ash rice husk and know the rate irrigate the best gel silica fromvarious concentration when compared to kiesel‐Gel 60. Research conducted in AnalitycalChemistry laboratory Analyze the FMIPA UNY during month February‐ June 2010.Research method used are the incineration ash rice husk, preparation ofcondensation of sodium silicate (Na2SiO3). Making of gel silica, rate determinationirrigate the gel silica, and analyze qualitative from data of rate comparison irrigate andIR spectra coming near standard of kiesel Gel‐60.Result obtained from this research are (1) gel silica can synthesis from sodiumsilicate from ash rice husk by using hydrochloric acid with the concentration 1, 3, and 5M as form gel where optimal result of gel silica obtained from sodium silicate with acidsolution of chloride 5 M; (2) best water rate come near the standard of kiesel G‐60 is gelsilica by using chloride acid 5 M with the rate irrigate equal to 8.2610 %.Key words: dusty waste ash rice husk, gel silica, kiesel gel‐60